Cost-utility of screening for depression among asylum seekers: a modelling study in Germany - Biddle, Louise; Miners, Alec; Bozorgmehr, Kayvan (Health policy, 2019)
BACKGROUND: Asylum seekers have a high burden of mental illness owing to traumatic experiences before, during and after flight. Screening has been suggested to identify asylum seekers with psychosocial needs. However, little is known about the costs of screening relative to expected gains. We assessed the cost-utility of population-based screening for depression in German asylum reception centres compared to case-finding by self-referral. - METHODS: Explorative modelling study using a decision tree over 15 months to estimate the incremental cost per quality-adjusted life-year gained. Data points were taken from the published literature. Deterministic and probabilistic sensitivity analyses were used to address uncertainty around parameter estimates. Value of information analyses were performed to indicate the value of future research. - RESULTS: The model demonstrates a high probability (p = 83%) of the screening intervention being cost-effective at a Є 50,000/QALY threshold. Cost-utility depends on the process of care following screening: when acceptability and adherence parameters were decreased by 40%, the resulting ICER increased by 27-131%. Eliminating uncertainty was most valuable for the screening process and cost parameters, at Є 3·0 and Є 4·4 million respectively. - CONCLUSIONS: Screening asylum seekers for depression may be a cost-effective strategy to identify those in need of care. However, there is considerable value in conducting further research in this area, especially regarding resource requirements and the process of care following screening.
Gesehen am 11.03.2020